Analisis Teori-teori yang Menyimpang tentang Penebusan Kristus - Simanjuntak, Herbin; Simanjuntak, Radius; Ndruru, Yohanes (Jurnal Teologi Berita Hidup, 2025)
The atonement of Christ is a fundamental doctrine in Christian theology that affirms that His death and resurrection are the only way of salvation for mankind. However, throughout church history, various deviant theories have emerged, providing interpretations that contradict Christian orthodox teachings. This study aims to analyze deviant theories regarding the atonement of Christ, identify the factors causing these deviations, and compare them with doctrines that are in accordance with the teachings of the Bible. The research method used is a literature study by examining books and theological journals from a historical and systematic perspective. The results of the study show that deviations in the theory of atonement are often rooted in a mistaken understanding of the nature of Christ, God's justice, and the meaning of sacrifice and penal substitution in the work of salvation. Thus, this study is expected to provide deeper theological insight for Christians in maintaining the purity of the teachings of Christ's atonement in accordance with the truth of the Bible.